2018
DOI: 10.1093/arclin/acy021
|View full text |Cite
|
Sign up to set email alerts
|

Older Adult Normative Data for the Sniffin’ Sticks Odor Identification Test

Abstract: Normative performance on the SS-OIT for adults over the age of 50 was established in a large and demographically diverse sample. These data are needed in order for clinicians to be able to include olfactory testing, a sensitive marker of neurodegeneration, in their assessment armamentarium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
(30 reference statements)
1
3
0
Order By: Relevance
“…19 Evidence suggest that smoking impairs the olfactory function; 20 therefore, the higher female smoking prevalence in Europe could decrease their scores to the average of male. The finding in this cohort that women had more keen sense of smell appears to follow the general trend in olfaction research, 14,21,22 although there is still some conflicting evidence; 23,24 and indeed the absolute numerical differences here are small.…”
Section: Discussionsupporting
confidence: 55%
“…19 Evidence suggest that smoking impairs the olfactory function; 20 therefore, the higher female smoking prevalence in Europe could decrease their scores to the average of male. The finding in this cohort that women had more keen sense of smell appears to follow the general trend in olfaction research, 14,21,22 although there is still some conflicting evidence; 23,24 and indeed the absolute numerical differences here are small.…”
Section: Discussionsupporting
confidence: 55%
“…were 13 and 10, respectively [15]. Vickers et al [16] conducted normative data research of the Sniffin' Sticks odor identification test (SS-OIT) in adults. They found that age had a significant effect on SS-OIT.…”
Section: Discussionmentioning
confidence: 99%
“…A normative data study using a cultural adaptation of the Portuguese version of the Sniffin’ Sticks smell test found that the cutoff points of identification scores for hyposmia in participants aged 16–55 years and >55 years were 13 and 10, respectively [15]. Vickers et al [16] conducted normative data research of the Sniffin’ Sticks odor identification test (SS-OIT) in adults. They found that age had a significant effect on SS-OIT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation